The Global Child Labor Problem : What Do We Know and What Can We Do? - Basu, Kaushik; Tzannatos, Zafiris (Washington, DC: World Bank, 2014)
The problem of child labor has moved from a matter of regional and national concern to one of international debate and possible global persuasion and policy intervention. In crafting policy for mitigating this enormous problem of our times, it is important to start with a proper theoretical and empirical understanding of the phenomenon. What gives rise to child labor, and what are its consequences? What interventions might end child labor without hurting children? A well-meaning but poorly designed policy can exacerbate the poverty in which these laboring children live, even leading to starvation. The article surveys the large and rapidly growing literature on this subject, focusing mainly on the new literature based on modern economic theory and econometrics. It also looks at some of the broad policy implications of these new findings, with the objective of contributing to better informed discussion and policy design.